Effects of Nearly‐2D Oxygen Vacancy Clustering on the Magnetic Properties of d0 Systems: The Case of Anatase and Rutile TiO2. Issue 10 (29th August 2018) - Drera, Giovanni; Mozzati, Maria C.; Malavasi, Lorenzo; Galinetto, Pietro; Sangaletti, Luigi
Abstract : A comprehensive magnetic characterization in a set of rutile and anatase thin films grown on different substrates is reported. TiO2−δ films have been grown with the RF‐sputtering technique on various non‐magnetic substrates (fused silica, Al2 O3, LSAT); subsequently, a protocol of annealing procedures has been applied in order to alter the sample oxygen stoichiometry. Magnetic characterization has been carried out at each step of the films treatments. It is shown that control over oxygen stoichiometry can be used in these samples to induce room‐temperature ferromagnetism (FM). Percolation schemes developed for the anatase or rutile lattices are considered to show that FM is related to clustered oxygen vacancies. The values of saturation magnetization, determined from thin films in a wide thickness range (33–317 nm), indicate that ferromagnetic ordering can be explained on the basis of a magnetic layer hosting a percolating cluster related to oxygen vacancies at the interface with the substrate or at the film surface, the first being common to all samples, while the second being triggered by vacuum annealing. Abstract : Control over oxygen stoichiometry, attained by annealing either in oxygen or high vacuum conditions, is used to induce room‐temperature ferromagnetism in rutile and anatase TiO2 thin films grown by RF sputtering on LSAT, Al2 O3 or fused silica substrates. A percolating cluster of spin ½ polarons, confined at the film–substrate interface, is found to be at the origin of ferromagnetism.